2009
DOI: 10.1021/es902039x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Speciation of Copper in Secondary Fly Ash by X-ray Absorption Spectroscopy

Abstract: Although some researchers have reported that chlorides may play an important part in the evaporation of copper during heat treatment of municipal solid waste incinerators (MSWI) fly ash (1, 2) , details on the copper speciation in volatile matters (secondary fly ash, SFA) are still lacking. In this work, we used in situ X-ray absorption spectroscopy (XAS) experiments involving three types of SFA, which was collected from a high-temperature tubular electric furnace by thermal treatment of municipal solid waste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…In this study, the spectral characteristics of the Cu(II)-containing samples (Electronic Annex, Figure S1A) suggest that Cu is present in the +2 oxidation state (Palomino et al, 2000;Furnare et al, 2005a;Strawn and Baker, 2009;Tian et al, 2009). To further identify the detailed microstructures of Cu(II) in the sorption samples, the normalized XANES spectra were processed to produce their first derivative curves (Electronic Annex, Figure S1B).…”
Section: Xanes Spectramentioning
confidence: 95%
“…In this study, the spectral characteristics of the Cu(II)-containing samples (Electronic Annex, Figure S1A) suggest that Cu is present in the +2 oxidation state (Palomino et al, 2000;Furnare et al, 2005a;Strawn and Baker, 2009;Tian et al, 2009). To further identify the detailed microstructures of Cu(II) in the sorption samples, the normalized XANES spectra were processed to produce their first derivative curves (Electronic Annex, Figure S1B).…”
Section: Xanes Spectramentioning
confidence: 95%
“…2, the XENAS spectra of metallic Cu, Cu 2 O and CuO standards show the white line peaks at 8991.7, 8993.4 and 8995.6 eV, respectively, which correspond to 1s ? 4p transitions [30,31]. The Cu-TiO 2 shows a broad white line peak at 8993.5-8997.8 eV, suggesting the Cu species is mainly deposited in the 2+ state.…”
Section: Characterization Of Cu-tiomentioning
confidence: 97%
“…Hsiao et al (2006) revealed that CuCl 2 , Cu(OH) 2 and CuO with a small amount of CuS were major copper compounds in fly ashes. According to Tian et al (2009), the copper in raw fly ash mainly existed as CuO and CuSO 4 Á5H 2 O, while copper chloride dominated all the content of fly ash at 1000°C. Even though copper species in MSWI fly ash was not identified, it seems Cu mainly vaporized in the form of chloride and higher temperatures accelerated the formation of copper chlorides (Belevi and Langmeier, 2000).…”
Section: Removal Of Heavy Metals From Fly Ashesmentioning
confidence: 99%